OPTIMALISASI PENGENDALIAN BANJIR DI KABUPATEN KEEROM PROPINSI PAPUA - Dance Manuel Agustinus Saroi; Harmonis Rante; Thobby Wakarmamu (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The river as a system is an ecological system that is very vulnerable to environmental changes. With environmental changes in a river system, the morphology of the river will also change, following the dynamics of ecosystem changes that occur. Flooding often causes damage to residential areas and infrastructure surrounding river basins. Some of the problems that cause flooding in Keerom district include the silting of the bottom and the many river bends that result in high sedimentation, especially in the Mur River in East Arso and the Tami River in West Arso. Therefore, it is necessary to plan a flood control design in Keerom Regency, which will serve as a technical guideline for the implementation of physical work later. From the results of the analysis using topographic data analysis methods, hydrological analysis, and flood discharge analysis on the Mur and Tami rivers, it can be concluded that the optimization of flood management that occurs in the East Arso Mur River and the West Arso Tami River is to build earthen embankments and install gabions in several transes, which are the overflow points of the Mur River and Tami River.